2021
DOI: 10.1021/acs.jpcb.0c09901
|View full text |Cite
|
Sign up to set email alerts
|

Surface Decoration of Cetyltrimethyl Ammonium Bromide on SiC Particles and Its Effects on the Co-Deposition Process

Abstract: Cetyltrimethyl ammonium bromide (CTAB) is used to decorate the SiC particle surface. The mechanism of the decoration process has been studied by simulation and experimental approaches. Molecular dynamics (MD) simulation finds a bilayer adsorbed structure of CTAB on the SiC particles, which is then verified by Fourier-transform infrared and thermal gravimetric analysis measurements. The MD simulation also finds that the decorative effects of CTAB on the SiC particle surface are related to the surface charge con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…20 The peak of CS-CTAB at 1457 cm À1 is the characteristic peak of the amine group from CTAB. 21 The characteristic peaks appearing at 1384 cm showed that the functional groups of CTAB were grafted successfully on the CS surface, which was consistent with the FT-IR spectral analysis results.…”
Section: Elemental Composition and Functional Groups Of Cs And Cs-ctabsupporting
confidence: 85%
See 1 more Smart Citation
“…20 The peak of CS-CTAB at 1457 cm À1 is the characteristic peak of the amine group from CTAB. 21 The characteristic peaks appearing at 1384 cm showed that the functional groups of CTAB were grafted successfully on the CS surface, which was consistent with the FT-IR spectral analysis results.…”
Section: Elemental Composition and Functional Groups Of Cs And Cs-ctabsupporting
confidence: 85%
“…The stretching vibration peaks of C=C appeared at 1618 cm −1 and 1616 cm −1 .The peak at 1541 cm −1 appears as a characteristic peak for the carbon skeleton vibration of C=C 20 . The peak of CS‐CTAB at 1457 cm −1 is the characteristic peak of the amine group from CTAB 21 . The characteristic peaks appearing at 1384 cm −1 and 1339 cm −1 are caused by the bending vibration of C‐H.…”
Section: Resultsmentioning
confidence: 98%
“…However, we expect surfactants such as cetrimonium bromide (CTAB) or perfluorooctanoic acid (PFOA) and perfluoro­octanesulfonic acid (PFOS) (with the same monovalent charge but a significantly higher number of polarizable electrons along the carbon tail and larger surface coverage) to elicit large, distinguishable differences in χ (2) and Φ(0) tot relative to the alkali cations. We also chose these species due to their environmental and technological relevance and specifically due to CTAB’s versatility of adopting multiple morphologies at interfaces that range from monomers to micelles to bilayers to adlayers. …”
Section: Introductionmentioning
confidence: 99%